ГЕОАХБОРОТ ТИЗИМЛАРИ ВА МАСОФАДАН ЗОНДЛАШ УСУЛЛАРИ ЁРДАМИДА ЯЙЛОВ ЕРЛАРНИ ТАДҚИҚ ҚИЛИШНИНГ ЧЕТ ЭЛ ТАЖРИБАЛАРИ - Жақсибаев, Р.Н.; Габбаров, С.Н.; Алеуов, А.С. (SCIENCE and SOCIETY, 2022)
The article studies the current experience of the condition of pastures in areas with ecological problems and the level of environmental impact on them using modern technologies, and provides recommendations for the use of modern methods in the study of vegetation of the Aral Sea regions and pastures.